GAME LEARNING IN FOREIGN LANGUAGE CLASSES AS A COMPONENT OF PROFESSIONAL AND PEDAGOGICAL FORMATION OF A FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2022)
In article day analysis particularities of the playing education on occupation on foreign language an forming professional pedagogical formation of the future teacher.
Keywords: playing education; play